A higher water-soluble phosphorus supplement in pig diet improves the whole system phosphorus use efficiency. (1st November 2020) - Liu, Ling; Guo, Yongqing; Tu, Yan; Zhang, Naifeng; Bai, Zhaohai; Chadwick, David; Dou, Zhengxia; Ma, Lin
Abstract: Low phosphorus use efficiency in livestock production has contributed greatly to the unsustainable depletion of phosphorus rock reserves, and to subsequent impacts on the environment. In this study, we compared the effects of two contrasting water-soluble phosphorus supplements on phosphorus use efficiencies through the 'rock mining – feed – pig – crop' system, as this whole system analysis has not been explored in previous studies. Weaned piglets were individually fed one of eight different diets that were formulated using two water-soluble phosphorus supplements, a high water soluble (HWS) and a low water soluble (LWS) supplement, at different levels of inclusion in the diet, and production indicators were measured. The total phosphorus content and different phosphorus fractions were measured in the resulting manure, and in the soil following manure application. At the whole system level, the diet supplemented with 0.20%HWS increased average daily gain and apparent total tract digestibility of feed phosphorus by 21.9% and 21.7%, and reduced manure total phosphorus and water soluble inorganic phosphorus by 37.7% and 43.9%, compared with the 0.20%LWS amended diet. The 0.10%HWS supplement increased phosphorus use efficiency of the whole system by 18.1%, compared to 0.20%LWS supplement. These results suggest that a shift of pig feed supplementation from lower to higher water-soluble supplements could be an effective strategy for sustainable phosphorus use through the whole pig production system, and provides new insights for sustainable livestock production in countries with severe challenges from phosphorus shortages and pollution. Graphical abstract: Image 1 Highlights: Impacts of feed P supplement on P use efficiency required a whole system analysis. The high water soluble P supplement reduced labile P in manure and need for P rock. The high water soluble P supplement enhanced P use efficiency of the whole system.